1989
DOI: 10.1364/josab.6.000329
|View full text |Cite
|
Sign up to set email alerts
|

Dark optical solitons with finite-width background pulses

Abstract: Using numerical solutions of the nonlinear Schrodinger equation, we show that for positive group-velocity dispersion, optical dark pulses superimposed upon background pulses only-10X wider can exhibit stable soliton propagation in single-mode fibers. During propagation the background pulse spreads (which reduces its intensity) and develops a frequency chirp. Nevertheless, as the background pulse evolves the dark pulse adiabatically maintains its soliton characteristics. These numerical results are in excellent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(36 citation statements)
references
References 12 publications
3
33
0
Order By: Relevance
“…We note that the calculated profile of the light beam at Fig. 4a whereas the dashed line shows the intensity distribution over the profile of the dark soliton I TC = I 1 tan 2 (x/a 1 ) [25], which can be obtained by solving the nonlinear Schro .. dinger equation for Kerr-type defocusing nonlinearity. Upon further propagation, the light beam loses power as a result of absorption and the region of localization experiences diffraction spreading.…”
Section: Discussion Nonlinear Absorption Of Singular Light Beamsmentioning
confidence: 99%
“…We note that the calculated profile of the light beam at Fig. 4a whereas the dashed line shows the intensity distribution over the profile of the dark soliton I TC = I 1 tan 2 (x/a 1 ) [25], which can be obtained by solving the nonlinear Schro .. dinger equation for Kerr-type defocusing nonlinearity. Upon further propagation, the light beam loses power as a result of absorption and the region of localization experiences diffraction spreading.…”
Section: Discussion Nonlinear Absorption Of Singular Light Beamsmentioning
confidence: 99%
“…The interaction between two ideal dark solitons is governed by an effective repulsive force in contrast with the force between two bright solitons, which depends on the relative phase of the solitons (Tomlinson and Hawkings 1989).…”
Section: Introductionmentioning
confidence: 99%
“…By utilizing specially shaped, antisymmetric input pulses, this group made the first clear observation of the fundamental dark soliton in single-mode fibers and demonstrated that at appropriate power levels the dark pulses propagate without broadening [10]. They also showed that even with a rapidly evolving background, dark pulses can exhibit stable soliton propagation [11]. They further investigated collisions of dark solitons in optical fibers [12], and, in another experiment, discovered temporal and spectral self-shifts of dark solitons propagating in single-mode fibers [13].…”
mentioning
confidence: 99%
“…We can qualitatively understand these phenomena in the following way. The gray pulse can be considered as a rapid dip in the intensity of a broad bright pulse [11]. During its propagation in the laser fiber, self-phase modulation (SPM) generates new frequency components that are red-shifted near the leading edge and blue-shifted near the trailing edge of the broad bright pulse.…”
mentioning
confidence: 99%
See 1 more Smart Citation